An umbrella of legitimacy: Rebel faction size and external military intervention. Issue 4 (September 2018) - Szentkirályi, Levente; Burch, Michael
How may the legitimacy of rebel groups shape the decisions of third-party states to support insurgencies militarily? In aiming to better understand how the (group-level) attributes of insurgencies motivate interventions on their behalf, we argue that the size of rebel forces serves as a proxy for a revolution's perceived legitimacy within the international community. Specifically, we maintain that the larger the insurgency, the greater the insurgency's perceived legitimacy and, thus, the more likely intervention on its behalf becomes. This analysis challenges previous studies that have confined the causal salience of faction size to relative capabilities or strength, and it also underscores the controversial policy implications of this finding.